Probabilitas Penurunan Pendapatan Pekerja Migran Indonesia di Masa Pandemi Covid-19 - Rusadi, Fadlila Mohd.; Anas, Yulia (Ekonomis: Journal of Economics and Business, 2025)
One of the impacts of the Covid-19 pandemic on Indonesian migrant workers is the decline in income of Indonesian Migrant Workers (IMW). This impact varies quite widely between groups of migrant workers when viewed from socio-economic characteristics which include worker categories, business fields, employment sectors, changes in working hours, education level and gender. This research aims to analyze the probability of a decrease in income during Covid-19 experienced by migrant workers based on socio-economic characteristics. The unit of analysis in this research is 109 individuals identified as IMW in the National Labor Force Survey data for the period August 2020. The results of research using probit regression analysis show that migrant workers who have a high probability of experiencing a decrease in income are blue-collar workers, workers in tertiary business fields, workers in the informal sector, workers with reduced working hours, workers with an education level below high school/vocational school/equivalent. However, in this study no significant results were found regarding differences in income based on gender.